Loan disbursement by financial services institutions: Determinants in Asia - Suwinto Johan; Wahyuni Rusliyana Sari (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
The economy of a country cannot be separated from the financing in the economic ecosystem of the nation. On the opposite, overly excessive funding will cause the economy of a country to become overheated. An overheated economy can harm the country's overall system. This research analyzes the variables that determine the distribution of financing by the financial services industry to private sectors. This research studies five variables as independent variables and private credit disbursement as the dependent variable. The independent variables are inflation interest rate, exchange rate, gross domestic product, and gross domestic product per capita. This research investigates the 31-year historical data collected from 11 countries in Asia. This study uses a balanced panel data model and E-views to process the data. The data is obtained from the World Bank website. This research concludes that inflation, gross domestic product, and exchange rate to United State Dollar have a significant influence on the distribution of private credit. Moreover, the gross domestic product per capita and interest rate does not influence the private credit distribution.